2021
DOI: 10.1038/s41366-021-00879-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, oxidative DNA damage and vitamin D as predictors of genomic instability in children and adolescents

Abstract: Background/objectives Epidemiological evidence indicates obesity in childhood and adolescence to be an independent risk factor for cancer and premature mortality in adulthood. Pathological implications from excess adiposity may begin early in life. Obesity is concurrent with a state of chronic inflammation, a well-known aetiological factor for DNA damage. In addition, obesity has been associated with micro-nutritional deficiencies. Vitamin D has attracted attention for its anti-inflammatory prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 96 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The accumulation of DNA damage, particularly in response to high-fat diets ( 30 , 31 ), is further supported by the presence of γH2AX foci, an early indicator of DNA double-strand breaks ( 32 ). Additionally, the correlation between overweight status in adolescents and lymphocytic DNA damage ( 33 ) and the association of obesity with various DNA lesions, including double-strand breaks and oxidative base damage, which are reflective of BMI and DNA damage indices ( 29 ), align with our observations. In the AHU group, significantly elevated dsDNA levels were observed compared to the HC group (see Figure 1 ), which is consistent with the metabolic syndrome phenotype characterized by obesity, dyslipidemia, and mild inflammation (see Table 1 , Figure 4 ).…”
Section: Discussionsupporting
confidence: 86%
“…The accumulation of DNA damage, particularly in response to high-fat diets ( 30 , 31 ), is further supported by the presence of γH2AX foci, an early indicator of DNA double-strand breaks ( 32 ). Additionally, the correlation between overweight status in adolescents and lymphocytic DNA damage ( 33 ) and the association of obesity with various DNA lesions, including double-strand breaks and oxidative base damage, which are reflective of BMI and DNA damage indices ( 29 ), align with our observations. In the AHU group, significantly elevated dsDNA levels were observed compared to the HC group (see Figure 1 ), which is consistent with the metabolic syndrome phenotype characterized by obesity, dyslipidemia, and mild inflammation (see Table 1 , Figure 4 ).…”
Section: Discussionsupporting
confidence: 86%
“…The association between DNA/RNA damage and chromosomal aberration has been documented. Usman et al confirmed that oxidative DNA damage in obese children is a predictor of genomic instability [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair deficiencies have been linked to aging, suggesting that interventions reducing the mutational nuclear or mitochondrial load and enhancing or rerouting repair mechanisms may slow aging and delay the onset of age-related diseases. VitD emerges as a potential intervention in this context [ 18 ].…”
Section: The Hallmarks Of Agingmentioning
confidence: 99%